The unequal functional redundancy of Arabidopsis INCURVATA11 and CUPULIFORMIS2 is not dependent on genetic background - Nadi, Riad; Juan-Vicente, Lucía; Mateo-Bonmatí, Eduardo; Micol, José Luis (Frontiers in Plant Science, 2023)
The paralogous genes INCURVATA11 (ICU11) and CUPULIFORMIS2 (CP2) encode components of the epigenetic machinery in Arabidopsis and belong to the 2-oxoglutarate and Fe (II)-dependent dioxygenase superfamily. We previously inferred unequal functional redundancy between ICU11 and CP2 from a study of the synergistic phenotypes of the double mutant and sesquimutant combinations of icu11 and cp2 mutations, although they represented mixed genetic backgrounds. To avoid potential confounding effects arising from different genetic backgrounds, we generated the icu11-5 and icu11-6 mutants via CRISPR/Cas genome editing in the Col-0 background and crossed them to cp2 mutants in Col-0. The resulting mutants exhibited a postembryonic-lethal phenotype reminiscent of strong embryonic flower (emf) mutants. Double mutants involving icu11-5 and mutations affecting epigenetic machinery components displayed synergistic phenotypes, whereas cp2-3 did not besides icu11-5. Our results confirmed the unequal functional redundancy between ICU11 and CP2 and demonstrated that it is not allele or genetic background specific. An increase in sucrose content in the culture medium partially rescued the post-germinative lethality of icu11 cp2 double mutants and sesquimutants, facilitating the study of their morphological phenotypes throughout their life cycle, which include floral organ homeotic transformations. We thus established that the ICU11-CP2 module is required for proper flower organ identity.